Tales of love, sex, and danger - Kakar, Sudhir; Ross, John Munder (New Delhi ; Oxford : Oxford University Press, 2011)
This book discusses the complexities of love and the nature of erotic passion as these appear in the great love stories of the world. Revised and updated, this new edition, published after a gap of 25 years, includes an Epilogue which re-evaluates the authors' assertions about romantic and erotic love in the context of contemporary psychoanalysis and modern literary theory.
Previous ed.: 1986.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references.
Keywords: Erotic literature -- History and criticism